2020
DOI: 10.1016/j.rser.2020.110049
|View full text |Cite
|
Sign up to set email alerts
|

A practical review of alternatives to the steady pressurisation method for determining building airtightness

Abstract: As an important indicator of construction quality and envelope integrity of buildings, airtightness is responsible for a considerable amount of energy losses associated with infiltration. It is crucial to understand building airtightness during construction and retrofitting to achieve a suitable envelope airtightness which is essential for obtaining a desirable building energy efficiency, durability and indoor environment. As a convenient means of measurement, the current steady pressurisation method has long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Due to being disruptive, time consuming and complex to operate, tracer gas based methods for measuring air infiltration are usually substituted with a measurement of building airtightness, which is then used to estimate the infiltration rate of the test building in conjunction with a leakage-infiltration relationship and sometimes environmental and terrain conditions. Although a number of airtightness testing methods are in existence such as acoustic [5,6,7] and unsteady pressurisation technique [8,9,10,11,12,13,14,15,16], the blower door is a convenient and reliable means for measuring building airtightness that has been widely adopted as the standard testing method in building regulations and voluntary standards. The measurement of building airtightness has become a regulatory requirement in many countries due to its impact to the building energy efficiency, indoor air quality and building durability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to being disruptive, time consuming and complex to operate, tracer gas based methods for measuring air infiltration are usually substituted with a measurement of building airtightness, which is then used to estimate the infiltration rate of the test building in conjunction with a leakage-infiltration relationship and sometimes environmental and terrain conditions. Although a number of airtightness testing methods are in existence such as acoustic [5,6,7] and unsteady pressurisation technique [8,9,10,11,12,13,14,15,16], the blower door is a convenient and reliable means for measuring building airtightness that has been widely adopted as the standard testing method in building regulations and voluntary standards. The measurement of building airtightness has become a regulatory requirement in many countries due to its impact to the building energy efficiency, indoor air quality and building durability.…”
Section: Introductionmentioning
confidence: 99%
“…It is also desirable to test the airtightness of a building at lower pressure differentials, such that the flow through the envelope will mimic that of a building under ambient pressures. Such factors have provided the research motivation to seek for alternative methods to overcome some of the issues shown in the steady pressurisation method [36].…”
Section: Conventional Airtightness Measurementmentioning
confidence: 99%
“…The term 'air leakage', another way of quantifying airtightness, has often been used to describe the integrity of the building envelope. It fundamentally determines the building infiltration rate, which is responsible for a significant amount of energy losses during heating or cooling the building [2,3,4,5,6,7,8,9,10,11,12]. In the long term, it also affects the indoor air quality and building durability [13,14].…”
Section: Introductionmentioning
confidence: 99%